Impact of alternative footwear on human balance. (1st September 2016) - Chander, Harish; Morris, Cody E.; Wilson, Samuel J.; Garner, John C.; Wade, Chip
Abstract : Alternative footwear are those that are most commonly used for casual or recreational purposes, over the course of the day. The purpose of this study was to examine the effects of three forms of alternative footwear (thong style flip-flops, clog style Crocs®, and Vibram Five-Fingers®) on balance with a low-intensity workload. Eighteen healthy male adults (age: 22.9 ± 2.88 years; height: 179 ± 6.0 cm; mass: 81.3 ± 8.8 kg) participated in this study. Balance performance along with electromyographic (EMG) measures was assessed with sensory organization test (SOT) and motor control test on the Neurocom Equitest, while donning alternative footwear, prior to and after a one-mile walk at a self-selected pace. Sway velocities and root-mean-square sway, SOT equilibrium scores, postural response latencies, and EMG measures from lower leg muscles were analysed using a 3 × 2 (footwear × time) repeated-measures ANOVA. Results from balance variables revealed a significant main effect difference for footwear in the eyes closed and eyes open sway-referenced vision conditions and a significant main effect difference for time in the eyes open, eyes open sway-referenced vision, and eyes open sway-referenced platform conditions. Pairwise comparisons revealed MIN demonstrating significantly greater balance performance in the pretest condition and the post-test demonstrating significantly lower balance performance. Greater balance performance from MIN could be attributed to the barefoot design suggesting an increase in somatosensory feedback from the plantar surface, particularly during absent or conflicting visual feedback. The lower balance performance seen in post-test could be attributed to the one-mile walk, suggesting that even a transient physiological workload could be sufficient to cause balance decrements in alternative footwear.